Profil Kemampuan Berpikir Kritis pada Pembelajaran Biologi Siswa Kelas XI IPA SMA PGRI Pekanbaru Tahun Ajaran 2022/2023 - Yola Yulianis; Suryanti Suryanti (Jurnal Simki Postgraduate, 2023)
This study aims to determine the profile of critical thinking skills in biology learning of class XI IPA SMA PGRI Pekanbaru in the 2022/2023 academic year. This research is a descriptive research. The method used in this study is a survey method. Data collection was carried out using questions, interviews, observation sheets and documentation. The sample in this study were 64 students, taken from class XI IPA students. The results showed that students' critical thinking skills belonged to the sufficient category with a percentage of 72%. It can be concluded that students in class XI IPA SMA PGRI Pekanbaru for the 2022/2023 Academic Year are quite capable of critical thinking in biology learning.